﻿Tadpole soup: Chinantec caldo de piedra and behavior of Duellmanohyla ignicolor larvae (Amphibia, Anura, Hylidae) - Carlos A. Flores; Medardo Arreortúa; Edna González-Bernal (ZooKeys, 2022)
Although amphibian consumption by humans has been reported globally, this practice is not well studied despite its direct implications to the decline of amphibian populations. The International Union for Conservation of Nature (IUCN) recognizes the need to document the use and trade of species to be considered in assessing their extinction risk. Here the consumption of Duellmanohyla ignicolor tadpoles is documented. It is a micro endemic species categorized as Near Threatened (NT) consumed in a traditional dish called “caldo de piedra” (stone soup) prepared by the Chinantec people (Tsa Ju Jmí’) in Oaxaca, Mexico. Through conversations with local people and stream monitoring, the behavior of tadpoles of this species was documented and aspects of their exploitation and habitat use described. Places where caldo de piedra is still consumed were determined and using a spatial analysis with Geographic Information Systems, the distribution of the species in relation to those localities was analyzed. A number of other areas where tadpoles of this species might also occur and be exploited is predicted. In conclusion, the school behaviour, surface feeding, and the preference for deeper waterbodies that these tadpoles exhibit makes them vulnerable to being caught in large quantities. As they are consumed locally, are not commercialized, and the species distribution range is wider than caldo de piedra consumption, this implies a low risk for their populations. However, the tadpoles’ reliance on streams with depths x̄ = 60 cm and flux x̄ = 0.65 m/s reduces the availability of sites for their optimal development.